Sistem Penilaian Kinerja Manajerial Departemen Produksi Studi Pada Usaha Snack di Pakis Malang - Made Iska Aprilita Wardani; Tasnim Nikmatullah Realita; Yudhi Anggoro (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
Performance appraisal is a way of determining the work results of employees and work groups that are useful if used the right methods on target and produce the desired conclusions according to output targets and performance standards. This research method is qualitative, namely observing performance appraisals that are already in effect with a combination of quantitative and qualitative methods. Quantitative by comparing work standards and output targets. Qualitative is assessed from skills (competence, physical abilities, coordination and teamwork); character (discipline, ability to make decisions and speed of response); and accuracy (supervision, control and the presence of work solutions).  Assessment data from January to April 2019. The time limit was chosen because the performance appraisal had stopped starting in August 2019, and required a remedial analysis. The results of the study show that performance appraisal provides an efficiency of 14% and makes assessments more noticed by all production employees. Methods collaborate in generating a more complete and mature assessment, as well as other suggestions for improvement. And prove that performance appraisal is useful for efficiency and effectiveness, controlling and monitoring performance, and being able to motivate employees to work even better.